The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1550-2783-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of phosphatidic acid ingestion on lean body mass, muscle thickness and strength gains in resistance-trained men

Abstract: BackgroundPhosphatidic acid (PA) has been reported to activate the mammalian target of rapamycin (mTOR) signaling pathway and is thought to enhance the anabolic effects of resistance training. The purpose of this pilot study was to examine if oral phosphatidic acid administration can enhance strength, muscle thickness and lean tissue accruement during an 8-week resistance training program.MethodsSixteen resistance-trained men were randomly assigned to a group that either consumed 750 mg of PA (n = 7, 23.1 ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 30 publications
(35 reference statements)
10
36
5
Order By: Relevance
“…Previous studies have used narrow field‐of‐view imaging snapshots at both the VL0 and VL5 locations to quantify MT, PA, and FL in the VL. However, little consensus exists regarding the rationale for anatomical landmark selection during ultrasound assessment of the VL.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have used narrow field‐of‐view imaging snapshots at both the VL0 and VL5 locations to quantify MT, PA, and FL in the VL. However, little consensus exists regarding the rationale for anatomical landmark selection during ultrasound assessment of the VL.…”
Section: Discussionsupporting
confidence: 91%
“…However, since the repeatability of measurement was not so good (the CV of repeated measurements was 13.5%), it may be the reason for the lack of changes in pennation angle. Hoffman et al 92) found an increase in VL thickness after resistance training for 8 weeks, but did not find such an increase in its pennation angle. Because the subjects in Hoffman et al 92) were resistance-trained men, and because adaptation of the pennation angle of VL was large within several weeks from the beginning of the training program 46) , the lack of change in the pennation angle of VL may have been due to its low responsiveness.…”
Section: Evidence Against Pennation Angle Changementioning
confidence: 92%
“…Hoffman et al 92) found an increase in VL thickness after resistance training for 8 weeks, but did not find such an increase in its pennation angle. Because the subjects in Hoffman et al 92) were resistance-trained men, and because adaptation of the pennation angle of VL was large within several weeks from the beginning of the training program 46) , the lack of change in the pennation angle of VL may have been due to its low responsiveness. Lack of pennation angle adaptation was also demonstrated in MG 93,94) and BF 56) , but these studies did not provide data on changes in muscle size.…”
Section: Evidence Against Pennation Angle Changementioning
confidence: 92%
See 1 more Smart Citation
“…With regards to human studies, one resistance exercise training study has employed oral supplementation of PA, producing an increase in lean body mass compared to placebo (Hoffman et al, 2012). …”
Section: How Can a Mechanical Signal Elicited By Resistance Exercise mentioning
confidence: 99%